The Effect of Flashcard Media on the Outcomes of Subject on the Introduction to Pancasila Symbols for Grade II of UPTD SD Negeri 122384 Pematangsiantar - Parno Sitinjak; Osco Parmonangan Sijabat; Minar Trisnawati Lumbantobing (International journal of technology and education research, 2026)
This study aims to determine the effect of flashcard media on students’ learning outcomes in Pancasila Education, specifically on the topic of recognizing Pancasila symbols, among second-grade students at UPTD SD Negeri 122384 Pematangsiantar. This research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The sample consisted of 20 students. Data were collected through tests administered before (pretest) and after (posttest) the implementation of flashcard media in the learning process. The results of data analysis showed a significant improvement in students’ learning outcomes after the treatment. Hypothesis testing revealed that the calculated t-value (tcount = 10.012) was higher than the critical t-value (ttable = 1.729) at a significance level of 0.05. Since tcount > ttable, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. This indicates that there is a significant effect of using flashcard media on students’ learning outcomes in Pancasila Education. The findings suggest that flashcard media is an effective instructional tool for enhancing students’ understanding of abstract concepts such as Pancasila symbols. The visual and interactive nature of flashcards helps students to learn more actively, increases engagement, and improves retention of learning materials. Therefore, it can be concluded that the use of flashcard media has a positive and significant effect on the learning outcomes of second-grade students in Pancasila Education at UPTD SD Negeri 122384 Pematangsiantar.